Penjadwalan Maintenance Mesin Jumbo Roll Tissue (JRT) Menggunakan Model Age Replacement - Dermawan, Dedi; Yul, Faradila Ananda; Nurzen, Muhammad; Denur, Denur (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
PT. Pindo Deli Pulp and Paper Tbk is an industry in the field of paper and tissue production. The processing system is one of the factors influencing production results. Maintenance measures must be an important concern. Based on observations and looking at data on machine maintenance costs, it is known that the largest cost incurred by the company in carrying out JRT machine maintenance is IDR 256,000,000, which if it continues will be detrimental to the company. To minimize expenses and optimize component performance, it is necessary to analyze maintenance/replacement policies using the Age Replacement method. One component that is experiencing quite large costs is Unwinder 1, which will be determined by scheduling replacement and maintenance using Age Replacement. Based on the results of data processing using Age Replacement, a replacement schedule for Unwinder 1 components was obtained, namely 10 months with cost savings of IDR 248,444